A systematic review of factors influencing Type 2 Diabetes Mellitus management in Nigerian public hospitals. (2019) - Bosun-Arije, Foluke Stella; Ling, Jonathan; Graham, Yitka; Hayes, Catherine
Abstract: Introduction: Type 2 Diabetes Mellitus (T2DM) is often a preventable type of Diabetes Mellitus (DM). However, if developed, can be managed effectively, even at a low-or-no cost. A critical evaluation of the literature on T2DM management in Nigeria reveals sparse evidence-base surrounding external and internal context-specific factors influencing T2DM management in public hospitals across Nigeria. Identification of these factors is crucial to health policy, research, and patient management. This review provides holistic evidence about the influencing factors in public hospitals across Nigeria. Methods: We synthesised quantitative studies on T2DM management, published between 2006 and 2016 in Nigerian public hospitals. Searches of PsycINFO, EMBASE, and Google Scholar databases were undertaken, alongside the African Journals Online (AJOL) and the Cochrane Library resources. The websites of the World Health Organisation African Region (WHO, AFR) and International Diabetes Federation African Region (IDF, AFR) were also searched. The Critical Appraisal Skills Programme (CASP) and Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) checklists were used for quality appraisal and report. Results: This review revealed factors such as non-adherence/non-compliance (20 studies), self-care related (9 studies), psychological-related (6 studies), social-related (6 studies), cost-related (6 studies) and drug-related (3 studies). Impacts of these factors on patient health outcome were elevated glycaemic levels, poor self-management skills, early development of DM complications, and loss of trust in clinical management as well as high mortality rate. Conclusion: The outcome of this review offers practical recommendations for policy review and suggestions for potential change implementation to improve T2DM patient management in the context of clinical practice.